Hubungan Pemanfaatan Dana Bantuan Operasional Kesehatan (BOK) Dengan Peningkatan Cakupan Kunjungan Antenatal K4 Di Puskesmas Kab. Konawe Tahun 2020 - Herlina Abidin (Jurnal Kesehatan Masyarakat Celebes, 2021)
Realization of BOK in the 2017 and 2019 Konawe Districts (100%), whereas 2018 (75%). As for gate of Dana BOK which is Allocated to the 2017 s/d 2019 KIA Program : Unaaha Public Health Center is average (27,17%), Wonggeduku Public Health Center is avarage (21,54%), Abuki Public Health Center is average (18,75%) and Soropia Public Health Center is avarage (36,09%). Whereas the absorption of the BOK fund to support the 2017 s/d 2019 Antenatal Activity Program that is: Unaaha Public Health Center is average (81,21%), Wonggeduku PHC is avarage (55,81%), Abuki PHC is average (88,10%) and Soropia PHC is avarage (68,77%). The study uses case studies with retrospective research design. Primary and secondary data sources. Primary data obtained directly from a (seven-person) informant through the interview process. Whereas secondary data are collected through the removal of documents to relating the polices of the KIA Program particulary activities supporting the K4 visit financed by the BOK funds. Studies are retrospective and interviews are carried out at the Konawe District Health Service and the four Public Centers that is: Unaaha PHC, Wonggeduku PHC, Abuki PHC and Soropia PHC.